0188 Speak Up! What Are The Barriers To Challenging Seniors?. (1st November 2014) - Beament, Tanja; Mercer, Simon
Abstract : Background: Recent high-profile cases of medical errors within a culture, where individuals felt unable to speak up, suggest that failure to challenge erroneous decisions contributes to patient morbidity and mortality. 1 "Responsible" followers are team-members with interpersonal skills, which allow for decisions of leaders to be challenged without contributing to a defensive or risk adverse culture. 2 It is crucial to identify those effective interpersonal skills and possible barriers to challenging seniors. Previous work suggests that simulation sessions incorporating erroneous decisions, can promote appropriate leadership challenges. 3 This project attempts to explore reasons for failure in a safe simulation environment and identify actual or perceived barriers to challenging senior anaesthetists to guide further medical education. Methodology: 20 CT1/2 anaesthetic trainee volunteers from our deanery will be invited to participate in a high-fidelity simulation scenario. Candidates will be randomly allocated to one of 2 standardised scenarios (scenario 1: surgeon requesting administration of wrong antibiotic triggering anaphylaxis. Scenario 2: consultant anaesthetist fixated on intubation despite patient desaturation). Scenarios will be videoed and watched during debriefing and each candidate asked to "think aloud" 4 to identify behaviours and "barrier themes". The debrief conversation will be transcribed, coded and analysed qualitatively using NVivo software. A phenomenological approach to data analysis, contrasting emerging themes with a control group will be adopted. Quantitative measurements will be undertaken to allow for triangulation. Results and potential impact: Using a mixed strategy, we will explore the dynamics of the trainee-supervisor relationship, and reflect on its implications to the timely delivery of safe care. Identifying possible barriers and underlying frames for trainees' challenging behaviours and time-lag for challenging seniors can suggest effective strategies to challenge erroneous decisions. This research will be advanced further as a team-skills workshop, where human factors, CRM and successful techniques for challenging can be developed. References: Belyansky I, Martin TR, Prabhu AS. Poor Resident Attending Intraoperative Communication May Compromise Patient Safety. J Surg Res 2011;171:386–94 Grint K, Holt C. Followership in the NHS. London, UK: King's Fund. 2011 Moneypenny MJ, Guha A, Mercer SJ, et al . Don't follow your leader: Challenging erroneous decisions. British Journal of Hospital Medicine 2013;pp. 1–8 Fonteyn ME, Kuipers B, Grobe SJ. A Description of Think Aloud Method and Protocol Analysis. Qualitative Health Research 1993;3(4):430–41